DEVELOPING STUDENTS’ COLOR PERCEPTION AND COMPOSITION SKILLS IN VISUAL ARTS LESSONS THROUGH AN INTEGRATED APPROACH - Murodova Shohinabonu Alisher qizi (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2026)
This article examines the pedagogical potential of using an integrated approach to develop students’ color perception and composition skills in visual arts lessons. The study explores methods that combine interactive techniques, digital resources, and project-based activities to enhance both creative and technical competencies. Findings indicate that an integrated approach makes lessons more engaging, fosters students’ creative thinking, and improves pedagogical effectiveness in visual arts education.